COMMUNICATIVE APPROACH IN TEACHING UZBEK LANGUAGE TO FOREIGNERS - Usmonova Zamira Jaxongirovna (Bright Mind Publishing, 2025)
The Uzbek language is distinguished by its rich history, culture and traditions. The process of teaching the Uzbek language to foreigners allows not only to teach the language, but also to get to know the Uzbek culture, customs and way of life. The communicative approach is very important in this process. The communicative approach is one that aims to develop not only theoretical knowledge, but also practical skills in language learning. This approach teaches students how to use language in real life and engages them in communication.
Keywords: Communicative approach, teaching methodology, independent thinking, simulation, group work, competition.